Tarpaper sky [compact disc] - Crowell, Rodney (New West Records, 2014)
Esteemed musician, songwriter and author Rodney Crowell has teamed up with New West Records to release Tarpaper Sky, his new self-produced album. This album also marks a reunion of the creative partnership of Crowell and musical accomplice Steuart Smith, who was an integral part of his overall sound during the late 80s.